Development of Learning Media Based on Adobe Flash CS6 in Vocational Theory Subjects of Clothing Decoration Making - Chusna Tsani, Romadhona; Widowati, Trisnani; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2019)
This research was conducted based on the results of observations and interviews which found out that 65% of students in Fashion Design did not meet the minimum completeness criteria (KKM) in the subject of Clothing Decoration Making because the media used by the teacher did not motivate students to learn. The purpose of this research study is (1)developing learning media based on Adobe Flash CS6 in the Vocational Theory of Clothing Decoration Making, (2)analyzing the feasibility and practicality of instructional media, (3)analyzing the effectiveness of the use of instructional media. The research development of learning media based on Adobe Flash CS 6 uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluations). The data collection tool for the feasibility of instructional media uses expert validation questionnaires namely material experts and media experts. Data on the practicality of the media used an assessment questionnaire by teachers and students. Data on the effectiveness of the media used question instruments. The validity test of the questionnaire instrument used Aiken's V formula, and the question instrument was validated with the product moment correlation formula. The reliability test of the questionnaire instrument used Cohen's Kappa, while the reliability test of the question instrument used the Split-Half technique. The results of eligibility by material experts were known as 91% in the very feasible category and media experts at 81% in the very feasible category. The effectiveness of Adobe Flash CS6 based media using the t test showed that .the significance value was 0,000> 0.05. So it can be concluded that there were significant differences. The N-gain test result was 77.9% which is included in the effective category. Based on the results of the analysis of these data, learning media can be used by fashion students at SMK Negeri 1 Sayung as an effective learning media for Vocational Theory Subjects of Clothing Decoration Making.